Must conditional cash transfer programs be conditioned to be effective?: The impact of conditioning transfers on school enrollment in Mexico - de Brauw, Alan; Hoddinott, John F. (International Food Policy Research Institute, 2008)
A growing body of evidence suggests that conditional cash transfer (CCT) programs can have strong, positive effects on a range of welfare indicators for poor households in developing countries. However, the contribution of individual program components toward achieving these outcomes is not well understood. This paper contributes to filling this gap by explicitly testing the importance of conditionality on one specific outcome related to human capital formation (namely school enrollment), using data collected during the evaluation of Mexico’s Programa de Educación, Salud, y Alimentación (PROGRESA) CCT program. We exploit the fact that some PROGRESA beneficiaries who received transfers did not receive the forms needed to monitor their children’s attendance at school. We use a variety of techniques, including nearest neighbor matching and household fixed effects regressions, to show that the lack of these forms reduced the likelihood of children attending school, with this effect being most pronounced among children who were transitioning to lower secondary school. We provide substantial evidence that these findings are not driven by unobservable characteristics related to households or localities.